Interactions of cotton with CBD peptides - Paulo, Artur Cavaco (1999)
The binding of genetically engineered Family II cellulose binding domains (CBDs) of Cellumonas fimi cellulases to cotton fabrics was studied and possible textile applications were investigated. Family II CBDs bound to cotton cellulose increased dye affinity, especially for acid dyes, but with very poor washing fastness. Ironing of the protein bound fabrics before dyeing increases dye affinity, which is probably due to protein denaturation and thus increases exposition of ionic groups. For desorption of CBD proteins from the cotton fabric, high levels of mechanical agitation and alkaline conditions (pH >7) are necessary. Binding of Family II CBDs to cellulose releases fine particles, whereas migration and desorption did not. Long time storage of cotton fabrics with adsorbed CBD proteins did not cause changes in their physical properties and did not damage cotton cellulose. The presence of water on the surface of cellulose was found to be essential for the interfabric migration of Family II CBDs. The double binding cellulose domain binds strongly on cotton and their interfabric migration is smaller. (C) 1999 Elsevier Science Inc. All rights reserved.